Energy Efficient Green Building Based on Geo Cooling System in Sustainable Construction of Malaysia - Alam, Md. Rabiul; Zain, M.F.M.; Kaish, A.B.M.A. (International Journal of Sustainable Construction Engineering and Technology, 2012)
This paper is focused to utilize geo energy in cooling of building in tropical country like Malaysia where temperature rises in daytime and goes beyond to a comfortable limit. In daytime inside temperature of the room is considered to be reduced by adding thermal conductivity media inside the room elements such as walls through its connectivity to the underground where temperature is less than the ambient room temperature. Due to the ground connectivity of thermal conductivity media a flow of heat creates from the room to the ground and tries to produce a thermal balance between these two medias and therefore, room temperature drops to a temperature close to the underground soil temperature. Aluminium pipes are considered as high thermal conductivity material. The entire study is done numerically using ANSYS 11 finite element software to determine the role of underground soil and thermal conductivity pipes. In numerical investigation heat flow between two systems (building rooms equipped with thermal conductivity pipe and underground soil) is studied and the performance of the conductivity materials is examined. The room temperature in the presence of thermal conductivity media as well as mechanical cooling system is also investigated in this study. It is seen that high thermal conductivity media plays a role in transferring heat from room to the ground and makes cooling of the building effectively. It acts also effectively when it uses with other mechanical cooling system of building.